PENYULUHAN POLA HIDUP BERSIH DAN SEHAT (PHBS) PADA ANAK PANTI ASUHAN RAHMAH AL ASRI BANJARMASIN - Isnani, Nazhipah; Muliyani, Muliyani; Akbar, Nabila Hadiah; Zaini, Muhammad (Jurnal Bakti untuk Negeri, 2025)
Clean and healthy living behavior is behavior that is implemented by each person with their own awareness and carried out continuously every day to achieve the level of health needed to live a healthy and active life. Children need to know about PHBS because children are the group most vulnerable to disease, especially school-aged children. The aim of this community service is so that orphanage children are exposed to and receive information about PHBS so they can apply it in their daily lives. The method of this service activity is carried out through lectures and discussions held at the orphanage. The participants who attended were 12 orphanage children along with the orphanage management. The results obtained from this activity were that participants had quite high interest. This can be seen from the enthusiasm of the children in paying attention to the explanation and asking and providing answers to the speaker's questions.